2019
DOI: 10.1111/psyp.13366
|View full text |Cite
|
Sign up to set email alerts
|

Nightmares do result in psychophysiological arousal: A multimeasure ambulatory assessment study

Abstract: Individuals who frequently experience nightmares report compromised sleep quality, poor daytime mood, and functioning. Previous research has aimed at linking these impairments with altered sleep architecture, but results were inconclusive. One plausible explanation is that only a few studies recorded markers of autonomic nervous system activity. For the first time, this study collected such markers under ecologically valid conditions with ambulatory assessment. In 19 individuals with frequent nightmares (≥1 ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 71 publications
3
38
3
Order By: Relevance
“…Negatively toned dreams are associated with higher stress levels (De Koninck & Brunette, 1991 ), and nightmares are accompanied by increased autonomic activity and sympathetic tone (Paul et al, 2019 ; Perogamvros et al, 2019 ). Although it's unclear which specific mechanisms are involved in the brain that experiences frequent nightmares, as outlined by Nielsen and Levin ( 2007 ), norepinephrine may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Negatively toned dreams are associated with higher stress levels (De Koninck & Brunette, 1991 ), and nightmares are accompanied by increased autonomic activity and sympathetic tone (Paul et al, 2019 ; Perogamvros et al, 2019 ). Although it's unclear which specific mechanisms are involved in the brain that experiences frequent nightmares, as outlined by Nielsen and Levin ( 2007 ), norepinephrine may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that days with higher stress are associated with increases in negative emotions and rumination, as well as dysregulated cortisol patterns the next day (Sladek et al, 2020). Higher stress is also associated with less nocturnal blood pressure dipping (Holt-Lunstad et al, 2009;Smart Richman et al, 2010) and higher nocturnal heart rate (Paul et al, 2019), which may indicate elevated nighttime arousal and increase risk for nightmares. Future studies should examine possible psychophysiological mediators of links between daily stress and nightmares.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study highlighted that the activation of the autonomic nervous system could be associated with nightmares [161]. Paul et al [161] hypothesized that nightmares, as a kind of psychological stressor, would activate two different autonomic responses.…”
Section: Dreaming Across the Lifespanmentioning
confidence: 99%
“…A recent study highlighted that the activation of the autonomic nervous system could be associated with nightmares [161]. Paul et al [161] hypothesized that nightmares, as a kind of psychological stressor, would activate two different autonomic responses. They found an increase in heart rate frequency, breathing cycle length, electrodermal responses, and REM sleep density, showing increased autonomic activity in people who experienced nightmares [161].…”
Section: Dreaming Across the Lifespanmentioning
confidence: 99%
See 1 more Smart Citation